Stimulus‐Responsive Amino Acids Behind In Situ Assembled Bioactive Peptide Materials. (16th November 2022) - Song, Yanqiu; Zhang, Zeyu; Cao, Yawei; Yu, Zhilin
Abstract: In situ self‐assembly of peptides into well‐defined nanostructures represents one of versatile strategies for creation of bioactive materials within living cells with great potential in disease diagnosis and treatment. The intimate relationship between amino acid sequences and the assembling propensity of peptides has been thoroughly elucidated over the past few decades. This has inspired development of various controllable self‐assembling peptide systems based on stimuli‐responsive naturally occurring or non‐canonical amino acids, including redox‐, pH‐, photo‐, enzyme‐responsive amino acids. This review attempts to summarize the recent progress achieved in manipulating in situ self‐assembly of peptides by controllable reactions occurring to amino acids. We will highlight the systems containing non‐canonical amino acids developed in our laboratory during the past few years, primarily including acid/enzyme‐responsive 4‐aminoproline, redox‐responsive (seleno)methionine, and enzyme‐responsive 2‐nitroimidazolyl alanine. Utilization of the stimuli‐responsive assembling systems in creation of bioactive materials will be specifically introduced to emphasize their advantages for addressing the concerns lying in disease theranostics. Eventually, we will provide the perspectives for the further development of stimulus‐responsive amino acids and thereby demonstrating their great potential in development of next‐generation biomaterials. Abstract : Amino acid toolkit exhibiting stimulus‐responsiveness allows for establishment of a considerable number of in situ peptide assembling systems via rational incorporation into peptide backbones, thereby serving as a versatile strategy for precise formation of bioactive materials at pathological sites with disease therapeutic and diagnostic functions.